The polarized spectral energy distribution of NGC 4151. Issue 1 (3rd June 2020) - Marin, F; Le Cam, J; Lopez-Rodriguez, E; Kolehmainen, M; Babler, B L; Meade, M R
ABSTRACT: NGC 4151 is among the most well-studied Seyfert galaxies that does not suffer from strong obscuration along the observer's line of sight. This allows to probe the central active galactic nucleus (AGN) engine with photometry, spectroscopy, reverberation mapping, or interferometry. Yet, the broad-band polarization from NGC 4151 has been poorly examined in the past despite the fact that polarimetry gives us a much cleaner view of the AGN physics than photometry or spectroscopy alone. In this paper, we compile the 0.15–89.0  μ m total and polarized fluxes of NGC 4151 from archival and new data in order to examine the physical processes at work in the heart of this AGN. We demonstrate that, from the optical to the near-infrared (IR) band, the polarized spectrum of NGC 4151 shows a much bluer power-law spectral index than that of the total flux, corroborating the presence of an optically thick, locally heated accretion flow, at least in its near-IR emitting radii. Specific signatures from the atmosphere of the accretion structure are tentatively found at the shortest ultraviolet (UV) wavelengths, before the onset of absorption opacity. Otherwise, dust scattering appears to be the dominant contributor from the near-UV to near-IR polarized spectrum, superimposed on to a weaker electron component. We also identify a change in the polarization processes from the near-IR to the mid-IR, most likely associated with the transition from Mie scattering to dichroic absorption from aligned dust grains in the dusty torus or narrow-line region. Finally, we present and discuss the very first far-infrared polarization measurement of NGC 4151 at 89  μ m.